Classification of ski resorts in Europe - Marina Georgigevna Krapivina; Irina Nikolayevna Tikunova (Наука. Инновации. Технологии, 2022)
The use of the multivariate classification method allowed defining two groups of parameters («primary» and «auxiliary»), whose sum is a criterion for the attractiveness of ski resorts for tourists (the «index of tourist attractiveness of ski resorts»). This formal method revealed territorial differentiation of domestic and international ski resorts. Analysis of characteristics of ski resorts in the European tourist region showed differences not only in the level of infrastructure and scale of services, but also in their specialty. The main types of ski resorts considering all provided services are classic skiing, family, snowboarding, and extreme.